PENGARUH KOMBINASI LAPISAN PAPAN PARTIKEL DARI LIMBAH PARTIKEL AREN (Arenga pinnata) DAN LIMBAH SERUTAN BAMBU (Dendrocalamus asper) DENGAN JUMLAH PEREKAT UREA FORMALDELHIDA TERHADAP SIFAT PAPAN PARTIKEL - Muhammad Lutfi Sonjaya; Iman Haryanto; Kusnanto - (ASEAN Journal of Systems Engineering, 2013)
The need of wood for lumber industry in indonesia has got deficit over increasing population that make demand increase dramatically. One of effort that we could do is to find an alternative of wood like make particle board. Sugar palm waste and bamboo waste can be usde as board particle sources because it contains sellulose, hemisellulose and lignin as element of wood structure. The objective of this research is to find out the effect of urea formaldehyde addition and combination of layered particle from aren waste particle and bamboo waste shaving to the properties of particle board.Research methodology was completely randomized design with two factors. The first factor has three kind treatment were combination layered board particle with ratio  face (sugar palm) : core (bamboo) : face (sugar palm) are 10%:80%:10%(K1), 20%:60%:20%(K2), 30%:40%:30%(K3). Second factor has three kind treatment were amount of adhesicve 5% (P1), 10%(P2) and 15%(P3). Parameter of property test were density, water absorption, thickness swelling, internal bonding, modulus of rupture and modulus of elasticity with using SNI 03-2105-2006.The research showed that particle layered composition factor affects significantly to internal bonding and modulus of elasticity but it doesn’t effect significantly to density, water absorption, thickness swelling and modulus of rupture. Meanwhile, adhesive factor affects significantly to all of property test. The best particle board made from combination layered arrangement 10% face : 80% core : 10% face (K1) with amount of adhesive 15% (P3). It has the best property as density 0,77 g/cm3, thickness swelling 22,84%, water arsoption 59,79%, internal bonding 3,56 kgf/cm2, modulus of rupture 182,48 kgf/cm2 and modulus of elasticity 16.352,9 kgf/cm2. Based on SNI 03-2105-2006, the properties test that had fullfilled were density, modulus of rupture and internal bonding but for water absorption, thickness swelling and modulus elasticity has not fullfill yet.